JUSTIFICATION OF THE TYPE AND VOLUME OF RESERVE OF ELEMENTS RECONNAISSANCE-FIRE SYSTEM - Karavanov, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2023)
The results of the analysis military conflicts of the last decades [1–4] indicate an increase in the share of tasks involving the destruction of targets by reconnaissance-fire systems (RFS). However, as the weight of these systems increases, the volume of measures to counteract them increases [3–5]. According to [6], the more effective a weapon sample is, the more efforts are made to neutralize it. That is, the greater the role RFS in the confrontation, the more effort is devoted to fighting them, therefore, the less stable its functioning will be, which in turn will lead to a decrease in the effectiveness of their use.